From Synagogue to Church : the traditional design : its beginning, its definition, its end - Wilkinson, John, 1929-2018 (Routledge Jewish studies series., 2014)
The designs of synagogues and churches are acknowledged to be very alike. But the designers' procedure was confidential, and so far standard explanations have been unsatisfactory. A synagogue should express heavenly values with earthly materials. This combination was in fact expressed in numbers, for, as Plato said, they linked heaven and earth. Scripture described both the Jewish Tabernacle and Temple with a wealth of numbers. Proportions based on these numbers were used to design synagogues. Only a few Jewish documents survive, but they reveal a symbolism, which Christians sometimes repe.